Paradigma presoje koncentracij v ZDA - Podobnik, Klemen (Podjetje in delo, 2015)
The paper analyses the development of the US antitrust law in the field of merger review, underlining especially the classic schism in the doctrinal approach that spreads on the axis between two extremes; a purely economic view on one side and the democratic efficiency view on the other side. In its extreme form, the former is mainly characterized by excessive trust in the criterion of economic efficiency, while the latter recognizes the broader implications of the accumulation of economic power stemming from unbridled concentrative processes. Based on the analysis of the relevant case-law and especially the theoretic achievements of the proponents of the two schools, the author concludes that the antitrust law should be perceived as a constitutional matter also in the field of mergers and acquisitions whereby it represents the instrument capable of establishing a reasonable and equitable relationship between the power of capital on one hand and individuals on the other.
Keywords: Das Kapital; kapital; koncentracija; koncerni; moč; podjetja; power; United States of America; ZDA; združevanje